2018
DOI: 10.1111/bjso.12235
|View full text |Cite
|
Sign up to set email alerts
|

Identity fusion predicts endorsement of pro‐group behaviours targeting nationality, religion, or football in Brazilian samples

Abstract: A visceral feeling of oneness with a group - identity fusion - has proven to be a stronger predictor of pro-group behaviours than other measures of group bonding, such as group identification. However, the relationship between identity fusion, other group alignment measures and their different roles in predicting pro-group behaviour is still controversial. Here, we test whether identity fusion is related to, but different from, unidimensional and multidimensional measures of group identification. We also show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 47 publications
0
43
0
6
Order By: Relevance
“…First we examined the correlation between fusion and group identification across the full sample and found that the variables were moderately correlated, n = 560, r s = .57, p < .001. This moderate level of correlation was anticipated, as previous studies have reported similar levels while still finding divergent validity between the constructs (Bortolini et al, 2018;G omez et al, 2011;Swann et al, 2009).…”
Section: Hypothesis 2: Levels Of Affective Arousal During Promotion Rmentioning
confidence: 50%
See 1 more Smart Citation
“…First we examined the correlation between fusion and group identification across the full sample and found that the variables were moderately correlated, n = 560, r s = .57, p < .001. This moderate level of correlation was anticipated, as previous studies have reported similar levels while still finding divergent validity between the constructs (Bortolini et al, 2018;G omez et al, 2011;Swann et al, 2009).…”
Section: Hypothesis 2: Levels Of Affective Arousal During Promotion Rmentioning
confidence: 50%
“…This moderate level of correlation was anticipated, as previous studies have reported similar levels while still finding divergent validity between the constructs (Bortolini et al, 2018;G omez et al, 2011;Swann et al, 2009). This moderate level of correlation was anticipated, as previous studies have reported similar levels while still finding divergent validity between the constructs (Bortolini et al, 2018;G omez et al, 2011;Swann et al, 2009).…”
Section: Hypothesis 2: Levels Of Affective Arousal During Promotion Rmentioning
confidence: 67%
“…Given these differences it is not surprising that fusion and group identification are associated to different variables or differ in regard to their predictive power, as several studies indicate. Bortolini, Newson, Natividade, Vázquez, and Gómez (2018), for instance, measured fusion and identification (in this case with multidimensional and unidimensional scales) with three different groups to compare their effects on pro‐group behavior. Their studies found that fusion explained further variance than each of the identification measures.…”
Section: Misconceptions About Identity Fusionmentioning
confidence: 99%
“…Pese a que la escala se ha utilizado en numerosos estudios, las propiedades psicométricas de la EVFI han sido reportadas en solo dos investigaciones (Bortolini, Newson, Natividade, Vázquez & Gómez, 2018;Gómez, Brooks et al, 2011). Gómez, Brooks et al (2011) construyeron la EVFI tanto en castellano como en inglés, y dieron evidencia de la estructura interna del test reportando una estructura unifactorial (CFI=.989; NFI=.987; GFI=.991; RMSEA=.053) y bifactorial (CFI=.971; NFI=.969; GFI=.977; RMSEA=.083) con los siete ítems de la escala.…”
unclassified
“…Es importante mencionar que Gómez, Brooks et al (2011) realizaron su investigación en tres muestras de diferentes culturas (i.e., estadounidenses, españoles e inmigrantes en España). En el contexto brasileño, Bortolini et al (2018) adaptaron la EVFI al idioma portugués, y además analizaron sus propiedades psicométricas, dando evidencia de la estructura interna del test, reportando un buen ajuste de la estructura unifactorial de siete ítems (CFI>.95; TLI>.95; RMSEA<.08). Además, dieron evidencia de invarianza métrica del test en tres grupos de referencia diferentes (i.e., nacionalidad, religión y fanáticos del futbol).…”
unclassified